The perspective of hypertension and salt intake in Chinese population - Jiang, Kexin; He, Tingting; Ji, Yongzhi; Zhu, Tao; Jiang, Enshe (Frontiers in Public Health, 2023)
Salt intake is too high nowadays. It has been widely recognized that there is a close relationship between hypertension (HTN) and dietary salt intake. Investigations reveal that long-term high salt intake, mainly sodium intake, induces a relevant increase in blood pressure in hypertensive and normotensive individuals. According to most scientific evidence, a diet with high salt intake in public increases cardiovascular risk, salted-related HTN, and other HTN-associated outcomes. Given the clinical importance, this review aims to present the prevalence of HTN and trends in salt intake in the Chinese population and will comprehensively discuss the risk factors, causes, and mechanisms of the association between salt intake and HTN. The review also highlights the education of Chinese people regarding salt intake and the cost-effectiveness of salt reduction from a global perspective. Finally, the review will emphasize the need to customize the unique Chinese practices to reduce salt intake and how awareness changes people's eating lifestyle and helps adopt diet salt reduction strategies.